Cartografias digitais da educação ambiental: a perspectiva do vídeo web - Silva, Janaína Oppermann e (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
Discusses the involvement of environmental education from the perspective of imagetechnologies. Proposes to web vídeo as a device in the representations of the environment andcultural artifact. It addresses the broad production of new digital processes (devices and methods)and discusses its potential in promoting awareness of look at daily. The Vídeo Web is place inenvironmental education to enhance the perception and in this vein, the use of digitaltechnologies as a result bring the vídeo experience shared while revealing the socioenvironmentalreality. The vídeo report expands the possibilities of collective perception,therefore, to seek solutions to their peers with common environmental problems, provides asituation of co-authorship. Thus, the relationship with nature and with the surroundingenvironment is recreated through the establishment of new meanings and concepts of the world.